EFFECTS OF THE IMPLEMENTATION OF THE IRE IN THE AGRICULTURAL SECTOR - Mariano Caballero Algarín, Félix; Antonio Zarza Cubilla, Carlos (Revista Gênero e Interdisciplinaridade, 2023)
The development of this work is based on the implementation of the Corporate Income Tax, the objective being to determine the effects of the implementation of the IRE in the agricultural sector. The applied approach was mixed, while the level of research was descriptive. It was held in Ciudad del Este; The population was 50 accountants working in the agricultural sector, of which 20 accountants were selected for the sample. The selected data collection technique was the survey.